The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/08854726.2021.1903734
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and Loved Ones’ Expectations of Chaplain Services

Abstract: A study assessing the expectations patients and loved ones have of hospital chaplains was conducted at Ascension St. Vincent Indiana hospitals. In-person interviews were conducted with 452 patients and loved ones during an inpatient stay. The survey instrument was a modified version of a survey developed by Dr. Katherine Piderman of the Mayo Clinic. Participants answered questions regarding demographics, awareness of availability, expectations of visits, reasons for wanting to see a chaplain and gave feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Furthermore, the role of chaplains in medical decision-making has gained additional visibility in recent years [ 41 ]. Most of these publications described chaplains' in-hospital role in family conferences or with palliative care teams but have not addressed periviable delivery contexts other than stillbirths [ 26 , [42] , [43] , [44] , [45] ]. Utilizing chaplain decision coaches with patients at risk of periviable delivery expands chaplains' skills to a population whose spiritual care needs were previously underserved by chaplains.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the role of chaplains in medical decision-making has gained additional visibility in recent years [ 41 ]. Most of these publications described chaplains' in-hospital role in family conferences or with palliative care teams but have not addressed periviable delivery contexts other than stillbirths [ 26 , [42] , [43] , [44] , [45] ]. Utilizing chaplain decision coaches with patients at risk of periviable delivery expands chaplains' skills to a population whose spiritual care needs were previously underserved by chaplains.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the delivery location of many spiritual care visits in the inpatient setting. 30,31 However, spiritual care by phone is becoming increasingly acceptable in chaplaincy practice—especially given recent experiences with the COVID-19 pandemic. 17,20,32,33 Spiritual care delivered by phone has notable benefits similar to virtual visits for clinical care: the care recipient is able to engage with a chaplain in a meaningful way without having to travel long distances, arrange childcare, or take extended time off from work, thus removing some barriers associated with healthcare access.…”
Section: Discussionmentioning
confidence: 99%
“…They can support older adults in the search for meaning in life, reconciliation with (past) life, experiencing peace and hope, coping with death, and in reflecting on and deepening the role of spirituality in one’s life (Prause et al, 2020 ; Timmins et al, 2018 ; Visser et al, 2023 ; Wells et al, 2021 ). Recent research has shown that patients feel satisfied when they receive chaplaincy care and that their spiritual needs are met (Kirchoff et al, 2021 ; Marin et al, 2015 ; Muehlhausen et al, 2022 ; Tan et al, 2020 ). Also, patients highly appreciate the chaplain's presence, trusting relationship, attentive listening, and familiarity (McCormick & Hildebrand, 2015 ; Sailus, 2017 ).…”
Section: Introductionmentioning
confidence: 99%